Decision Making Empowerment Among Women With And Without Microcredit Coverage (Journal of Preventive and Social Medicine, 2022)
Background: Women of Bangladesh, especially rural women experience adverse situations in terms of socioeconomic inequality and gender disparity. This study compared the decision making empowerment among women with and with microcredit coverage.Methods: The study design was a cross sectional study in two sample situation. Total 258 women, 129 with microcredit coverage and 129 without microcredit, was selected by convenience sampling technique from Pakdy and Thantoly of Madaripur district in Bangladesh. Data were collected by face to face interview with the help of a semistructured questionnaire. Data were analyzed by SPSS software. Quality control and ethical issues were maintained strictly.Results: The study revealed that mean (±SD) age of women with microcredit coverage was 30.27(±9.62) years and women without microcredit coverage was 30.78(±8.98) years. Mean (±SD) score of decision making empowerment was significantly higher among women with microcredit (34.02±3.92) than without microcredit (17.89±5.20) (p